Afrophloeus, a new genus of African weevils of the tribe Embrithini (Coleoptera: Curculionidae: Entiminae), with description of a new species and notes on the composition of Embrithini - Borovec, Roman; Oberprieler, Rolf G (Zootaxa, 2013)
A new genus, Afrophloeus gen. n., is described for three South African weevil species assigned to the tribe Embrithini Marshall: Trachyphloeus spathulatus Boheman (type species), T. squamifer Boheman and Afrophloeus dilaticornis sp. n. Afrophloeus squamifer has been introduced to Australia in 1992 and become an agricultural pest in South Australia in recent years. All three species are illustrated and keyed. The concept and composition of Embrithini is discussed and revised. Thirteen genera are newly transferred to Embrithini: Bryochaeta Pascoe, Cosmorhinus Schoenherr, Cycliscus Schoenherr, Glyptosomus Schoenherr, Porpacus Schoenherr and Syntaphocerus J. Thomson from the tribe Oosomini Lacordaire and Bicodes Marshall, Goniorhinus Faust, Holorygma Marshall, Lecanophora Aurivillius, Neobicodes Hustache, Sympiezorhynchus Schoenherr and Zeugorygma Marshall from the tribe Myorhinini Marseul. Two genera are excluded from Embrithini, Epibrithus Marshall and Rhyncholobus Gahan, left without tribal assignment in Entiminae. In its revised concept the tribe Embrithini includes 67 genera of African Entiminae.
Keywords: nosatcovití; mužské pohlaví; Jižní Austrálie; Species Specificity; ženské pohlaví; rozšíření zvířat; druhová specificita; zvířata; South Australia; Weevils; Female; South Africa; Jihoafrická republika; Male; Animal Distribution; Animals